Women In Utah History Paradigm Or Paradox? - Scott, Patricia Lyn; Thatcher, Linda (University Press of Colorado, 2005)
A project of the Utah Women's History Association and cosponsored by the Utah State Historical Society, Paradigm or Paradox provides the first thorough survey of the complicated history of all Utah women. Some of the finest historians studying Utah examine the spectrum of significant social and cultural topics in the state's history that particularly have involved or affected women.